DALE ESA - Beeh, Jos Josia; Suwartiningsih, Sri; Kudubun, Elly Esra (KRITIS, 2018)
The village Bokonusan is the location on the Semau Island and the district of Kupang, East Nusa Tenggara. Norma and refers to the contructual obligations between members of society in accordance with the rules of the costums, trust that refer to expectation and goals together in building in accordance with the values of mutual cooperation of solidarity of the community. As for the porpouse of research to, give me a description of application of the local Dale Esa in the life together in the village Bokonusan, as well as explain the elements of what is contained in the wisdom of Dale Esa as social capital in communities Bokonusan village. The method used is a qualitatve and approach to the contructivism oh the research descriptive aksplanative. Interwoven ily tradition, a marriege, birth, death, a new garden work (teh management of the land) and conflic resolution. The application of valeu to keep in daily life as from of social interaction. In the wisdom of Dale Esa the cooperation between the community refers to social relationships between societies so that, the social network, the obligation, prohibition, the rigth have, between members of the community to help each other as a from social norm, the emergance of the hope and goals together to build together as result the trust.